2016
DOI: 10.1021/acsami.6b00187
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Ice Adhesion on Nonsmooth Metallic Surfaces: Wettability and Topography Effects

Abstract: The effects of ice formation and accretion on external surfaces range from being mildly annoying to potentially life-threatening. Ice-shedding materials, which lower the adhesion strength of ice to its surface, have recently received renewed research attention as a means to circumvent the problem of icing. In this work, we investigate how surface wettability and surface topography influence the ice adhesion strength on three different surfaces: (i) superhydrophobic laser-inscribed square pillars on copper, (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 70 publications
4
85
1
Order By: Relevance
“…However, it is now realized that SHS is not always effective in reducing the ice adhesion, therefore surface wettability alone cannot predict the ice adhesion due to the complicated adhesion mechanism existing in liquid–solid and ice–solid systems . Kulinich et al found that when the rough morphology surface was gradually damaged during icing and deicing cycles (as shown in Figure A), ice‐phobic properties of the materials are weakened.…”
Section: The Mechanisms Of Anti‐icing and Icephobicitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is now realized that SHS is not always effective in reducing the ice adhesion, therefore surface wettability alone cannot predict the ice adhesion due to the complicated adhesion mechanism existing in liquid–solid and ice–solid systems . Kulinich et al found that when the rough morphology surface was gradually damaged during icing and deicing cycles (as shown in Figure A), ice‐phobic properties of the materials are weakened.…”
Section: The Mechanisms Of Anti‐icing and Icephobicitymentioning
confidence: 99%
“…[169] However, it is now realized that SHS is not always effective in reducing the ice adhesion, [170][171][172][173][174] therefore surface wettability alone cannot predict the ice adhesion due to the complicated adhesion mechanism existing in liquid-solid and icesolid systems. [175] Kulinich et al found that when the rough morphology surface was gradually damaged during icing and deicing cycles (as shown in Figure 7A), ice-phobic properties of the materials are weakened. Additionally, when droplets condensed in the rough structure, the ice nucleation would occupy the surface asperities, and lead to strong ice adhesion on such surfaces.…”
Section: Ice Adhesion Mechanismmentioning
confidence: 99%
“…In the recent years, many researches have been focusing on developing environmental friendly passive icephobic surfaces that can repel the incoming cold water droplets, [3][4][5][6] delay ice nucleation, [7][8][9] and reduce ice adhesion strength. [10][11][12][13][14][15][16][17] Since ice formation on the surface was proven to be inevitable under harsh environment, numbers of studies have been devoted to develop surfaces with low ice adhesion strength (<100 kPa). [18][19][20][21][22][23][24][25] To date, one of the most famous icephobic surfaces, the slippery liquid-infused porous surfaces (SLIPS), had achieved ultralow ice adhesion strengths of ∼15, 24 1.7, 26 and 0.4 kPa, 27 in different studies.…”
Section: Introductionmentioning
confidence: 99%
“…In these contexts, droplets usually evolve from a phase change on a cold substrate, and significant research is directed toward understanding the vapor condensation, deposition or liquid freezing processes in order to mitigate formation on the material surface. Most substrates tested exhibit varying degrees of hydrophobicity since anti-wetting or ice-shedding characteristics are desirable for a wide variety of applications, especially those wishing to prevent water or ice accumulation [4,5]. Interestingly, relatively less attention has been focused on the melting of a frozen droplet on such surfaces, which is especially relevant considering that active heating is a common anti-icing technique.…”
Section: Introductionmentioning
confidence: 99%